Dual color luminescence of Mn2+ doped lead-free Cs3Cu2I5 perovskite phosphors and their LED solid-state lighting and anti-counterfeiting applications. (August 2023) - Zhang, Jingwei; Han, Yonghua; Zhang, Li; Zhu, Hancheng; Song, Ting; Yan, Duanting; Zhang, Meng; Wang, Chao; Zhang, Xintong
Highlights: Solid state ball milling method is adopted to synthesize of Cs3 Cu2–2x I5 :2xMn 2+ . Dual color luminescence can be realized by Mn 2+ doped Cs3 Cu2 I5 . Mn 2+ doped Cs3 Cu2 I5 can be used for white light LEDs and anti-counterfeiting. Abstract: Cs3 Cu2 I5 have recently attracted far-flung and fervency interests with the characters of low cost, high photoluminescence quantum yield, green and non-toxicity. In addition, continuous tuning of the luminescence properties could be realized in Cs3 Cu2 I5, which would benefit its optical applications. Herein, Mn 2+ is chosen as the luminescent center into Cs3 Cu2 I5 through solid-state ball milling method. Its structure and photoluminescence properties have been studied by various characterization methods such as X-ray powder diffractions, fluorescence spectroscopy, and element mapping. These results showed that Mn 2+ doping into Cs3 Cu2 I5 makes little change on the crystal structure of Cs3 Cu2 I5 . The copper ions and manganese ions exist stably in the form of Cu + and Mn 2+, respectively. After Mn 2+ doping, a new emission peak appears at 560 nm except for the intrinsic blue emission of Cs3 Cu2 I5, thus realizing dual color luminescence. This material also exhibits excellent thermal stability, making it suitable for solid-state lighting and anti-counterfeiting applications. Graphical abstract: Image, graphical abstract After Mn 2+ doping, a new yellow emission appeared at about 560 nm which originated from the 4 T1 → 6 A1 transition of Mn 2+ . Thus, white color emission could be realized through the modulated relative intensities of the yellow emission together with the intrinsic blue emission.